The Effect of Private Investment, Government Spending and Labor on Economic Growth in Berau Regency, East Kalimantan Province - Sugianto, Bambang; Fadelan, Nahwani (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Economic growth shows the extent to which economic activity can generate additional income or public welfare in a certain period. The economic growth of a region that continues to show improvement, then it illustrates that the regional economy is developing well. This study aims to analyze the effect of partially and simultaneously private investment, government spending and labor on economic growth in Berau Regency. This research uses secondary data search and empirical and theoretical studies. The analytical tool used is multiple linear regression analysis. The entire data processing process was carried out with the help of the SPSS version 22 program using linear regression analysis. The results of the analysis show that partially private investment has a significant effect on economic growth with a contribution of 50.35%, government spending has a significant effect on economic growth with a contribution of 34.40% while labor partially has no significant effect on economic growth because it only contributes by 6.85%. However, simultaneously private investment, government spending and labor have a significant effect on economic growth in Berau Regency by 91.60%, meaning that the greater the incoming private investment